Haptic virtualisation of surfaces: feeling textiles on your phone - Annerose Braune (TU Dresden; Faculty of Mechanical Science and Engineering;Chair of Development and Assembly of Textile Products, 2021)
The haptic impression of textile surface properties has a decisive influence on its evaluation and ultimately on its acceptance and usability.  Many solutions are used to replicate a static contour or shape, e.g. to feel controls on common touch displays. In contrast, this project investigates whether it is possible to simulate the roughness or friction behaviour of a textile surface using a commercially available mobile device.